Pengaruh Pemahaman Bertransaksi Menggunakan Webform BSI dan BSI Mobile terhadap Kepuasan Nasabah - Yoannisa Fitrian Suhayati; Azri Nur Maulina; Widwi Handari Adji (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
With the change of digitalization transactions in Bank Syariah Indonesia, the mindset of bank customers and employees needs to be changed to familiarize themselves with using digital banking facilities, so that the realization of these habits requires understanding related to the use of digital banking to arise satisfaction in using it. This research aims to find out the knowledge of webform BSI and BSI mobile in transacting with customer libraries. This study hypothesizes that, partially, there is an influence between the understanding of transacting using webform BSI and customer satisfaction, and understanding transacting using BSI mobile somewhat affects customer satisfaction. The study used quantitative research methods and applied IBM SPSS version 23 as a test tool to aid data processing and data collection. The study had 89 respondents by sampling using incidental sampling techniques or by chance. This study revealed that the understanding of transacting using the webform BSI partially did not affect customer satisfaction, and the knowledge of transacting using BSI mobile partially affected customer satisfaction.